2018
DOI: 10.1080/17470218.2017.1363256
|View full text |Cite
|
Sign up to set email alerts
|

Cue competition influences biconditional discrimination

Abstract: When multiple cues are presented in compound and trained to predict an outcome, the cues may compete for association with an outcome. However, if both cues are necessary for solution of the discrimination then competition might be expected to interfere with solution of the discrimination. We consider how unequal stimulus salience influences learning in configural discriminations, where no individual stimulus predicts the outcome. We compared two hypotheses; (1) salience modulation minimises the initial imbalan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 28 publications
2
7
0
2
Order By: Relevance
“…That is, the same Passive rats that exhibited deficits in blocking were if anything better at solving complex nonlinear discriminations than their Agency counterparts. This finding is consistent with prior evidence that cue competition between the elements of a compound can hinder the solution of nonlinear discriminations 36 .…”
Section: Resultssupporting
confidence: 92%
“…That is, the same Passive rats that exhibited deficits in blocking were if anything better at solving complex nonlinear discriminations than their Agency counterparts. This finding is consistent with prior evidence that cue competition between the elements of a compound can hinder the solution of nonlinear discriminations 36 .…”
Section: Resultssupporting
confidence: 92%
“…Differences in the extent to which individuals use configurations of cues may still reflect differences in attention. Attentional breadth, a cognitive trait related to emotional arousal (Fredrickson, 2004), relates to an ability to solve configural discriminations such as negative patterning and biconditional discriminations (Byrom & Murphy, 2014, 2016b, 2017; see also McDonald et al, 1997, for an evaluation of the hippocampus in these tasks). Thus, while differences in ability to learn about multiple co-occurring stimuli may relate to some underlying ability to maintain or use task setting information, these differences may be related to attention.…”
Section: Example 3: Cs Processing Effects Schizotypy and Schizophreniamentioning
confidence: 99%
“…Note that this result is not surprising, since we anticipated that the color category might be easier to learn about. Unbalanced salience between stimuli has been shown to impair learning of biconditional discrimination in humans (Byrom & Murphy, 2019), and consequently, it could be the case that our stimuli, by virtue of their unequal saliences, prevented the transfer a configural processing to overshadowing training in group Biconditional. Additionally, other studies have shown that transfer effects enhancing configural processing were only reliable on the very first block of training of a subsequent discrimination (Mehta & Russell, 2009), suggesting that in general the transfer of the configural pretraining may be dependent upon very specific parameters of training or may be short lived (see Urcelay & Miller, 2010; Wheeler et al, 2008).…”
Section: Discussionmentioning
confidence: 99%